2019
DOI: 10.1080/15476286.2019.1669391
|View full text |Cite
|
Sign up to set email alerts
|

Interior circular RNA

Abstract: Formed by back splicing or back fusion of linear RNAs, circular RNAs (circRNAs) constitute a new class of non-coding RNAs of eukaryotes. Recent studies reveal a spliceosome-dependent biogenesis of circRNAs where circRNAs arise at the intron-exon junctions of mRNAs. In this study, using a novel de novo identification method, we show that circRNAs can originate from the interior regions of exons, introns, and intergenic transcripts in human, mouse and rice, which were referred to as interior circRNAs (i-circRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 62 publications
(82 reference statements)
2
35
0
Order By: Relevance
“…We characterized sub-exonic circRNA produced by nc genes in porcine species but the interest of this study goes beyond the pig genome. We note that the production of circRNA by the mono-exonic gene RNase_MRP was also reported in humans by Liu et al [44]. Using a similar method to the one we used in the present study, these authors identified a group of interior circRNAs.…”
Section: Discussionsupporting
confidence: 82%
“…We characterized sub-exonic circRNA produced by nc genes in porcine species but the interest of this study goes beyond the pig genome. We note that the production of circRNA by the mono-exonic gene RNase_MRP was also reported in humans by Liu et al [44]. Using a similar method to the one we used in the present study, these authors identified a group of interior circRNAs.…”
Section: Discussionsupporting
confidence: 82%
“…Even though we know that a few snoRNAs [ 20 , 29 ] are able to produce classical exonic circRNA, we did not detect any mono-exonic gene capable of producing exonic and sub-exonic circRNAs. We would like to underline the fact that also in humans, the production of a set of circRNAs by the mono-exonic gene RMRP (orthologous gene of porcine RNase_MRP ) was highlighted by Liu et al [ 42 ].…”
Section: Non-canonical Circrnas Are Even More Poorly Known Than Lamentioning
confidence: 99%
“…Further, due to circRNAs being highly conserved in many species, such as humans, nematodes, zebrafish, and mice ( Salzman et al, 2012 ; Li X. et al, 2019 ), only a small number of them can evolve and change rapidly ( Zhang et al, 2013 , 2014 ). Some studies point out that the number of circRNAs found in eukaryotic cells has been as high as more than 20,000 ( Cocquerelle et al, 1993 ; Westholm et al, 2014 ); a few are formed by direct cyclization of introns, and most of them come from exons ( Liu et al, 2020a ). In addition, as a kind of non-coding RNA, circRNA can only regulate the formation of proteins at the transcriptional or post-transcriptional level ( Westholm et al, 2014 ), and only a few of them can regulate life activities by encoding proteins ( Pamudurti et al, 2017 ; Yang et al, 2018 ).…”
Section: Overview Of Circrnasmentioning
confidence: 99%